Polyextremophile engineering: a review of organisms that push the limits of life - Caro-Astorga, Joaquin; Meyerowitz, Joseph T.; Stork, Devon A.; Nattermann, Una; Piszkiewicz, Samantha; Vimercati, Lara; Schwendner, Petra; Hocher, Antoine; Cockell, Charles; DeBenedictis, Erika (Frontiers in Microbiology, 2024)
Nature exhibits an enormous diversity of organisms that thrive in extreme environments. From snow algae that reproduce at sub-zero temperatures to radiotrophic fungi that thrive in nuclear radiation at Chernobyl, extreme organisms raise many questions about the limits of life. Is there any environment where life could not "find a way"? Although many individual extremophilic organisms have been identified and studied, there remain outstanding questions about the limits of life and the extent to which extreme properties can be enhanced, combined or transferred to new organisms. In this review, we compile the current knowledge on the bioengineering of extremophile microbes. We summarize what is known about the basic mechanisms of extreme adaptations, compile synthetic biology's efforts to engineer extremophile organisms beyond what is found in nature, and highlight which adaptations can be combined. The basic science of extremophiles can be applied to engineered organisms tailored to specific biomanufacturing needs, such as growth in high temperatures or in the presence of unusual solvents.